Effect of Diameter of Micropile on the Minaret Behavior during Earthquake, Virtual study (Journal of Engineering, 2022)
This study aims to suggest a technique for soil properties improvement of AL- Kadhimin shrine Minaret and to support the foundation, which has a tilt of roughly 80 cm from the vertical axis. The shrine of the AL- Kadhimin is made up of four minarets with two domes set in a large courtyard. The four minarets have skewed to varying degrees due to uncontrolled dewatering inside the shrine in recent years. However, the northeast minaret was the most inclined due to its proximity to the well placed inside shrine courtyard. When the well near the minaret is operated, the water level drops, increasing the effective stresses of the soil and causing differential settling of the minaret foundation. To maintain the minaret's foundation from potential lateral stresses, a micropile system has been proposed around it. PLAXIS 3D is used to do a three-dimensional numerical analysis in this study. A micropile system of several diameters has been considered for the suggested technique. In the analysis, the modeling and verification findings revealed that the suggested micropile system plays a significant role in incrementing the minaret's lateral load resistance (earthquake).